IDENTIFIKASI SEBARAN INDIKASI AIR TANAH DANGKAL TERKONTAMINASI LINDI DENGAN MENGGUNAKAN METODE RESISTIVITAS DAN INDUCED POLARIZATION (IP) DI SEKITAR TPA SAMBUTAN KOTA SAMARINDA - Bamba, Ayub; Supriyanto, Supriyanto (Geophysics Study Program, Faculty of Mathematics and Natural Sciences, Mulawarman University, 2019)
Sambutan of Samarinda City Landfill implements a sanitary landfill system in accordance with the applicable terms and conditions to minimize or eliminate environmental problems. This research was conducted around Sambutan of Samarinda which are in an area with coordinates 117 ° 06 '44.00